2019
DOI: 10.30699/sjhnmf.27.2.89
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Medication Adherence and Coping Skills in Patients With Heart Failure

Abstract: Introduction: Medication adherence is essential to improve outcomes emanated from the disease. The increase in the complexity of the medical regimens causes poor adherence in patients with heart failure; also, the progressive nature of Heart Failure (HF) and its complicated drug regimens are mostly stressful. This study has been conducted on the HF patients at the heart hospital of Kermanshah city with the objective of finding the association between medication adherence and coping skills. Methods: The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The results of another study also confirmed this finding 58 . Meanwhile, the results of another study showed that only 1.5% of patients with HF had high medication adherence 59 . The nature of disease, being acute or chronic, heavily influences the extent elderly' care for controlling their disease.…”
Section: Discussionmentioning
confidence: 99%
“…The results of another study also confirmed this finding 58 . Meanwhile, the results of another study showed that only 1.5% of patients with HF had high medication adherence 59 . The nature of disease, being acute or chronic, heavily influences the extent elderly' care for controlling their disease.…”
Section: Discussionmentioning
confidence: 99%